Parting the waters. Middle Palaeolithic archaeology in the central Ionian Sea - Galanidou, Nena (Journal of Greek Archaeology, 2018)
This paper sets out a conceptual framework based on the idea of connectivity, and the research design that informs a series of surveys and excavations in the central Ionian Sea targeting the Palaeolithic record. It highlights the importance of mapping the now submerged topography to get a better understanding of the relevant palaeogeography, and its wider implications for hominin settlement, landscape preferences and pathways of dispersal and expansion from mainland Greece into the Inner Ionian Archipelago and Lefkas. It argues that the sea and the offshore islands are not marginal or irrelevant but central to an understanding of Palaeolithic settlement and land use, especially during periods of low sea level. At these times, many islands would have become hills in an extensive coastal plain, representing ideal habitats for hunters and gatherers.